A One‐Dimensional Fluidic Nanogenerator with a High Power Conversion Efficiency. Issue 42 (7th September 2017) - Xu, Yifan; Chen, Peining; Zhang, Jing; Xie, Songlin; Wan, Fang; Deng, Jue; Cheng, Xunliang; Hu, Yajie; Liao, Meng; Wang, Bingjie; Sun, Xuemei; Peng, Huisheng
Abstract: Electricity generation from flowing water has been developed for over a century and plays a critical role in our lives. Generally, heavy and complex facilities are required for electricity generation, while using these technologies for applications that require a small size and high flexibility is difficult. Here, we developed a fluidic nanogenerator fiber from an aligned carbon nanotube sheet to generate electricity from any flowing water source in the environment as well as in the human body. The power conversion efficiency reached 23.3 %. The fluidic nanogenerator fiber was flexible and stretchable, and the high performance was well‐maintained after deformation over 1 000 000 cycles. The fiber also offered unique and promising advantages, such as the ability to be woven into fabrics for large‐scale applications. Abstract : Energy from flowing water : A new family of fiber‐shaped fluidic nanogenerators based on a sheet of aligned carbon nanotubes is created. A power conversion efficiency of 23.3 % is achieved by using the stable and durable nanogenerator. Its structure and performance can be well‐maintained even after 1 000 000 cycles of deformation.